Measuring wanting without asking: The Pavlovian-to-instrumental transfer paradigm under test. (December 2019) - Chillà, Chiara; Cereghetti, Donato; Cayeux, Isabelle; Porcherot, Christelle; Delplanque, Sylvain; Sander, David
Highlights: Efforts to obtain pleasant odours ("wanting") are influenced by rewarding properties (liking level). PIT is sensitive enough to measure "wanting" for odours with different rewarding properties. PIT is not more sensitive than liking ratings for odours with slightly different rewarding properties. Abstract: In consumer science, measuring liking is posited to be the best method to understand preferences and food choice behaviour. Consumer research shows that highly rewarding products are more often bought than slightly rewarding products. However, detecting clear differences in preferences for similarly rewarding products, which have just launched on the market, is not always easy to investigate with liking measures. Consequently, finding other methods measuring preferences for similarly rewarding products is necessary. A well-established theoretical framework used to study reward processing, the incentive salience theory, argues that the pursuit of a positive outcome depends on three distinct components: the motivation to obtain it ( wanting ), the pleasure felt during its consumption ( liking ), as well as its automatic associations and cognitive representations ( learning). The Pavlovian-to-Instrumental Transfer (PIT) paradigm is a promising method used to investigate wanting in animals and humans. The human PIT task has been used in the chemosensory field in the presence of a single odour. In the present methodological studies, we further investigated the sensitivity of the PIT task to measure cue-triggered wanting by comparing two olfactory rewards. The first study used two olfactory stimuli with very different liking levels, whereas the second used two olfactory stimuli with similar liking levels. The results suggested that the PIT task was sensitive enough to detect the effort participants mobilized (wanting) to obtain two olfactory stimuli with very different liking levels, which was not the case for olfactory stimuli with similar liking levels. Implications of the PIT task for consumer research were discussed.